2013
DOI: 10.1007/s11427-013-4480-6
|View full text |Cite
|
Sign up to set email alerts
|

pyrG is required for maintaining stable cellular uracil level and normal sporulation pattern under excess uracil stress in Aspergillus nidulans

Abstract: Tight control of the intracellular uracil level is believed to be important to reduce the occurrence of uracil incorporation into DNA. The pyrG gene of Aspergillus nidulans encodes orotidine 5′-phosphate decarboxylase, which catalyzes the conversion of orotidine monophosphate (OMP) to uridine monophosphate (UMP). In this study, we found that pyrG is critical for maintaining uracil at a low concentration in A. nidulans cells in the presence of exogenous uracil. Excess uracil and its derivatives had a stronger i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
2
7
0
1
Order By: Relevance
“…addition of uridine to the medium [4], being inhibited by high uracil concentrations [11]. A similar phenotype has been reported for uracil auxotrophs of A. nidulans [8]. Although not experimentally demonstrated, the growth-inhibitory effect of high uracil concentrations observed in A. nidulans pyrimidine auxotrophs was proposed to be linked with misincorporation of uracil into the DNA.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…addition of uridine to the medium [4], being inhibited by high uracil concentrations [11]. A similar phenotype has been reported for uracil auxotrophs of A. nidulans [8]. Although not experimentally demonstrated, the growth-inhibitory effect of high uracil concentrations observed in A. nidulans pyrimidine auxotrophs was proposed to be linked with misincorporation of uracil into the DNA.…”
Section: Resultssupporting
confidence: 61%
“…Candida famata) [5], Candida guilliermondii (syn. Pichia guilliermondii) [6], Aspergillus fumigatus [7] and Aspergillus nidulans [8]. Despite the importance of this apparently uncommon phenotype, it is poorly understood at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the EMP intermediates decreased while the citric acid precursors acetyl-CoA and oxaloacetate were significantly increased, it suggested that this metabolic change may be caused by the accelerated glycolysis pathway and the insufficient activity of the citrate synthetase. In Aspergillus nidulans, it is reported that the genes involved in carbon metabolism, such as α-glucosidase B (agdB) and sugar transporter, were significantly up-regulated in a pyrG deleted mutant [36], which is consistent with the EMP metabolism changes in this study. Therefore, we speculated that higher citrate synthetase expression could further improve citric acid production when pyrG expression was disrupted or reduced.…”
Section: Metabolite Profile Analysis Of a Niger D353 And Pyrg Disrupsupporting
confidence: 89%
“…Excess of exogenous uracil (but not uridine) was recently reported to have a strong inhibitory effect on the Aspergillus nidulans growth, being an auxotrophic strain deleted in pyrG (encoding orotidine-5 -phosphate decarboxylase) also more sensitive to uracil than the wild type strain (Sun et al, 2013). This uracil toxicity is believed to be related with the misincorporation of uracil into DNA when uracil is accumulated in excess (Sun et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This uracil toxicity is believed to be related with the misincorporation of uracil into DNA when uracil is accumulated in excess (Sun et al, 2013). Uridine cannot be directly incorporated into DNA, which may explain why excess uridine did not cause growth inhibition in A. nidulans (Sun et al, 2013) and A. gossypii.…”
Section: Resultsmentioning
confidence: 99%